(untitled) (Bangladesh Journal of Botany, 2024)
The methanol content and volatile aroma components were determined, and sensory evaluation and analysis were conducted. Results showed that the methanol contents of all the six sweet potato wine samples met the limits of the national standard, and a total of 258 volatile substances were detected. Among them, alcohols and phenols have the highest contents in the sample BBC-1 brewed in the family workshops, esters have the highest contents in the sample BBY-2 brewed in the distillery, acids and ketones have the highest contents in BBC-4 brewed in the family workshops, and aldehydes have the highest contents in BBY-1 brewed in the distillery. The sensory evaluation results showed that BBC-2 has the strongest and most elegant aroma, perfect typicality, and unique taste. The comprehensive evaluation results of BBY-2 are second only to BBC-2. The sweet potato wine samples BBC-2 and BBY-2 have better quality, and are suitable for promotion as the characteristic products of local sweet potato wine. These results can provide scientific basis for the improving the brewing process and quality of sweet potato wine industry in Xiapu County, Fujian Province. Bangladesh J. Bot. 53(3): 731-743, 2024 (September) Special